Informed consent: Old and new challenges in the context of the COVID-19 pandemic. Issue 1 (7th April 2021) - Rothwell, Erin; Brassil, Donna; Barton-Baxter, Marietta; Brownley, Kimberly A.; Dickert, Neal W.; Ford, Daniel E.; Kraft, Stephanie A.; McCormick, Jennifer B.; Wilfond, Benjamin S.
Abstract: In this paper, we address how the COVID-19 pandemic has impacted informed consent for clinical research through examining experiences within Clinical and Translation Science Award (CTSA) institutions. We begin with a brief overview of informed consent and the challenges that existed prior to COVID-19. Then, we discuss how informed consent processes were modified or changed to address the pandemic, consider what lessons were learned, and present research and policy steps to prepare for future research and public health crises. The experiences and challenges for CTSA institutions offer an important perspective for examining what we have learned about informed consent and determining the next steps for improving the consent process.